n vitro Antioxidant and Hepatoprotective Effect of the Whole Plant of Rungia repens (L.) Nees, Against CCl4 Induced Oxidative Stress in Liver Slice Culture Model - Anagha A. Rajopadhye,; Anuradha S. Upadhye, (International Journal of Phytomedicine, 2011)
Rungia repens (L.) Nees (Family-Acanthaceae) commonly known as ‘Pittapapda’ or ‘Khet papra’ is used in the treatment of various diseases in Indian system of Traditional Medicine. The present study aims to investigate antioxidant and hepatoprotective activity of hexane (RPH), ethanol (RPE) and water extract (RPW) of the whole plant of Rungia repens by employing photochemiluminescence and spectrophotometric methods. The results showed that RPE and RPW significantly inhibited DPPH, NO and SOD radical in dose dependent manner. The trade of phenol content was as: RPH (44 mg PCE/g) < RPW (154 mg PCE/g) < RPE (209 mg PCE/g). Significant correlation was shown by total phenol content and free radical scavenging activity of all three extracts. The hepatoprotective effect was assayed in CCl4-induced cytotoxicity in a liver slice culture model. The results revealed that significant depletion was observed in lactate dehydrogenase, lipid peroxidation, antioxidative enzymes SOD, CAT, and GR on administration of the RPE and RPW or ascorbic acid use as standard in the CCl4- induced cytotoxicity in the liver. Ethanol and water extracts of Rungia repens have prevented significant oxidative liver damage.